GEOLOGI DAN KARAKTERISTIK ENDAPAN MANGAN TIPE SEDIMEN DI DAERAH SUPUL KABUPATEN TIMOR TENGAH SELATAN PROVINSI NUSA TENGGARA TIMUR - , Evi Maria Ati, S.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Sedimentary manganese layers have been discovered in Supul, South Central Timor Regency, East â Nusa Tenggara Province. The manganese layers is associated with deep sea sedimentary rock and interbedded with redish to redish brown claystone. The deposit shows the spatial linkage with mud volcano intrusion. Physically, the manganese layers range from 2 mm to 4 cm in width, compact, lenticular, solid, and strongly deformed. Mineralogically, it is composed of manganite mineral (MnO(OH)) as primary mineral, pyrolusite (MnO2), lithiophorite (Al,Li) MnO2(OH)2, and associated with gangue minerals including calcite (CaCO3), silica (SiO2), limonite (FeO(OH), hematite (Fe2O3) and Barite (BaSO4). There are two form types of manganese ores that found in study area, that is manganese nodule and manganese layers. Mineralogically, the manganese nodule composed of manganite that associated with limonite. It has grade of 62.72 and 69.42 wt.% MnO. Whereas manganese layers classified into three form types. The first type is pyrolusite and has grade of 66.05 wt.% MnO. The second and third have different in the hardness. Mineralogically, the second and third types of manganese layer composed of manganite as primary manganese mineral, and also lithiophorite and pyrolusite. It has grade 63.33%-71.57 wt.% MnO. In general iron in Mn Ore is very low ranging from 0.2 to 1.54 wt.% Fe2O3, hence, Fe / Mn ratio is very low of 0.0025-0.0691%, which typically indicates sedimentary origin. This sedimentary origin is supported by petrologic and petrographic data showing layered structure of manganite and lithiophorite, as well as the degradation of crystal/grain size manganite. Geochemical analysis shows that manganese ore is non hydrothermal and was precipitated in reduction condition according to REE normalization graphic that revealing similar distribution pattern of REE with timor nodule, pacific hydrogenous and nodule hydrogenous that is the existing of Ce positive anomaly, graphic data of Co+Ni vs. As+Cu+Mo+Pb+V+Zn and the calculation of Ceanomaly. Moreover, this nodule manganese views hydrogenous deposit based on Al and Si concentration, and supported by the positive correlation of Mn with Cu, Ni and Zn, whereas the manganese layers is detrital diagenic deposit (remobilization of manganese in the water column of the ocean, precipitated and sedimented on the deep sea bottom) as well as reveals the effect of hydrothermal, which is the positive correlation of Mn and As. This is proven by the presence of quartz and barite veinlets cutting the Mn layers, manganite recrystallization along vei layers and the presence of pyrite. Geochemically supports the analysis mineralogically that is manganite which is one type of mineral manganese is relatively stable and in the solid phase has a balance of the sea water and are often not stable in oxidizing conditions so it was replaced by pirolusit. Based on field data and analysis of laboratory data, it shows that the formation of manganese layers deposit in study area is assumed due to the remobilization of manganese in the water column of the ocean, while the manganese nodules are hidrogenous deposits, formed by the chemical reaction within sea water shaping unsolvable particle in sea water so that it will be sink into the bottom of sea floor/precipitation of metals from sea water.